2021
DOI: 10.1111/cts.13159
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of celiprolol – evidence for a role of P‐glycoprotein and organic anion transporting polypeptide 1A2 in celiprolol pharmacokinetics

Abstract: The aim of this study was to search for associations of genetic variants with celiprolol pharmacokinetics in a large set of pharmacokinetic genes, and, more specifically, in a set of previously identified candidate genes ABCB1, SLCO1A2, and SLCO2B1. To this end, we determined celiprolol single‐dose (200 mg) pharmacokinetics and sequenced 379 pharmacokinetic genes in 195 healthy volunteers. Analysis with 46,064 common sequence variants in the 379 genes did not identify any novel genes associated with celiprolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Moreover, Hirvensalo et al . recently demonstrated that intestinal OATP1A2 and P‐glycoprotein play a role in the pharmacokinetics of celiprolol in humans, 42 further supporting the molecular mechanism underlying fexofenadine‐GT interaction through OATP1A2.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, Hirvensalo et al . recently demonstrated that intestinal OATP1A2 and P‐glycoprotein play a role in the pharmacokinetics of celiprolol in humans, 42 further supporting the molecular mechanism underlying fexofenadine‐GT interaction through OATP1A2.…”
Section: Discussionmentioning
confidence: 75%
“…However, recent highly sensitive proteomic analyses reported the expression of OATP1A2 in human jejunum and ileum samples. 37,39 Moreover, Hirvensalo et al recently demonstrated that intestinal OATP1A2 and P-glycoprotein play a role in the pharmacokinetics of celiprolol in humans, 42 further supporting the molecular mechanism underlying fexofenadine-GT interaction through OATP1A2.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that endothelin-1 (EDN1) may alter responses to β-adrenergic blockers, especially because TT carriers at the G5665T locus have a poor prognosis after β-blocker therapy ( 38 , 39 ). Absorption of β-blockers is also influenced by the multidrug transporter P-glycoprotein [expressed by the adenosine triphosphate (ATP)–binding cassette subfamily B member 1 (ABCB1) gene], whose gene polymorphism is associated with reduced AUC (area under the curve) for the drug ( 40 , 41 ). In addition, voltage-gated calcium channel α1C (CACNA1C) polymorphisms are associated with antihypertensive efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, celiprolol has been proposed as a sensitive clinical OATP2B1 probe 49 with supporting pharmacogenomic data to suggest that SLCO2B1 polymorphism affects celiprolol pharmacokinetics (PK) at the therapeutic dose 53 . However, in vitro transport of celiprolol was also shown to be mediated by intestinal OATP1A2 54 and a recent pharmacogenomic study suggested a possible involvement of intestinal OATP1A2 and P‐gp in celiprolol pharmacokinetics in humans 55 . The relative contribution between OATP2B1 and OATP1A2 needs to be understood before celiprolol can be recommended as a clinical probe for OATP2B1.…”
Section: Oatp2b1mentioning
confidence: 93%
“…53 However, in vitro transport of celiprolol was also shown to be mediated by intestinal OATP1A2 54 and a recent pharmacogenomic study suggested a possible involvement of intestinal OATP1A2 and P-gp in celiprolol pharmacokinetics in humans. 55 The relative contribution between OATP2B1 and OATP1A2 needs to be understood before celiprolol can be recommended as a clinical probe for OATP2B1.…”
Section: Ddis Involving Intestinal Oatp2b1mentioning
confidence: 99%